Social Media Technologies’ influence of Mobile Learning for Undergraduate Students in Malaysia - Ramakrishnan, Kalaimagal; Mohd Yasin, Norizan; Periyasamy, Jeyarani (International Journal of Psychosocial Rehabilitation, 2020)
In the 21st Century, Social media Technologies (SMTs) help the people in educational field. SMTs are widely used in Higher Learning Institutions (HLIs) to improve the students’ learning. However, there is a lack of research on this study in Malaysian HLIs. Previously, a paper on building the bridge between HLIs and SMTs through mobile learning in Malaysia has been published. Thus, this study offers a review to assess the knowledge of existing university digital resources and SMTs facilities which contribute to tacit and explicit knowledge sharing among ICT students in HLIs. It also identifies the impacts of SMTs in HLIs on both students and educators. This study is also unique in that it highlights how SMTs can be effectively connected to Mobile learning to support and enhance the Final year students’ learning in terms of contributing to tacit and explicit knowledge creation. By convenience sampling, 180 students and 32 academicians participated in the questionnaires, from 2 Malaysian private universities and 1 public university. The data was piloted before the final data collection step was carried out in December 2018. The study makes a valuable contribution, given that the SMTs positively and significantly relate to the students’ success in Malaysian HLIs